NF-κB-94ins/del ATTG Genotype Contributes to the Susceptibility and Imbalanced Th17 Cells in Patients with Immune Thrombocytopenia. (22nd July 2018) - Yu, Jie; Hua, Mingqiang; Zhao, Xueyun; Wang, Rui; Zhong, Chaoqing; Zhang, Chen; Wang, Ruiqing; Li, Guosheng; He, Na; Hou, Ming; Ma, Daoxin
Abstract : Background. The NLRP3 inflammasome plays important roles in the pathogenesis of autoimmune diseases. However, the role of the NLRP3 inflammasome in the pathophysiology of immune thrombocytopenia (ITP) remains unclear. Methods. RT-PCR was used to examine the polymorphism and expression of genes involved in the NLRP3 inflammasome in ITP patients. T helper cells and apoptosis of PBMC from ITP patients were analyzed by flow cytometry. The antiplatelet autoantibodies in plasma were determined by modified monoclonal antibody-specific immobilization of platelet antigens (MAIPA). Results . We found that the NF- κ B-94ins/del ATTG genotype contributed to the susceptibility of ITP. Furthermore, the platelet counts of ITP patients with the WW genotype or WD genotype were lower than those with the DD genotype of NF- κ B-94ins/del ATTG. Compared with controls, NF- κ B gene expression was significantly decreased and WW or WD genotype ITP patients displayed higher mRNA expression than DD individuals. Similarly, the mRNA expression of NLRP3 was also increased in the WW genotype. There was a significant gene dose effect of the percentage of Th17 cells for the WW, WD, and DD genotypes (WW < WD < DD) in the unstimulated group and no significant difference was found after being stimulated. The activation of the NLRP3 inflammasome could upregulate Th17 in ITP patients. Conclusion . The NF- κ B-94ins/del ATTG genotype might serve as a novel biomarker and potential target for ITP.